Technological Accessibility Plan for Students with Disabilities: An Experience in Inclusive Education - Delgado-Valdivieso, Karina (2023)
The Technological Accessibility Plan for Students with Disabilities (TAPSD) arises from the analysis and identification of the technological equipment needs of 212 children and adolescents with disabilities (CHAWD) from 5 educational institutions (regular and special) in Ecuador. 2.36% of CHAWD have mild disability, 22.17% moderate disability, 13.21% severe disability and 14.15% very severe disability. In addition, 32.54% use tablets, 23.58% smartphones and only 16.98% have a desktop computer. Due to the high percentages of students with intellectual, physical and cerebral palsy disabilities, very few are able to turn on the computer by themselves or use a tablet. TAPSD has been structured with these limitations in mind and the technical specifications of equipment, accommodations, and software to address learning and communication accessibility needs. It has been structured by means of files that show six experiences with methodologies to be used according to the different disabilities that they present.